Measuring Benefits of Government Investments (Washington D.C. : The Brookings Institution, 1965)
The book highlights discussion presented at a conference in brooking in November 1963 to explore the problems of appraising the benefits that are likely to accrue from proposed public investment projects.
Includes index
osc 14/06/17
Loans
Keywords: Investment